2022
DOI: 10.1162/neco_a_01498
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Pixel-Level Image Features From Two-Photon Calcium Signals of Macaque Visual Cortex

Abstract: Images of visual scenes comprise essential features important for visual cognition of the brain. The complexity of visual features lies at different levels, from simple artificial patterns to natural images with different scenes. It has been a focus of using stimulus images to predict neural responses. However, it remains unclear how to extract features from neuronal responses. Here we address this question by leveraging two-photon calcium neural data recorded from the visual cortex of awake macaque monkeys. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Our general framework for quantifying representational drift is versatile. By defining drift as a measure of the degradation of quality of a deep neural decoder trained on wavelet images, our exact method can be applied to any brain region, and any representation which can be decoded; calcium imaging data, for example, has been shown to be well suited to decoding using deep networks 21,32 . In this way our method can facilitate research into the drifting behaviours of a wide variety of neural representations and functionalities.…”
Section: Discussionmentioning
confidence: 99%
“…Our general framework for quantifying representational drift is versatile. By defining drift as a measure of the degradation of quality of a deep neural decoder trained on wavelet images, our exact method can be applied to any brain region, and any representation which can be decoded; calcium imaging data, for example, has been shown to be well suited to decoding using deep networks 21,32 . In this way our method can facilitate research into the drifting behaviours of a wide variety of neural representations and functionalities.…”
Section: Discussionmentioning
confidence: 99%
“…While the interaction between encoding and decoding has been explored for simple stimuli such as directional selectivity [55], the investigation of complex natural scenes has been limited due to constraints in computational models and methodologies [22], [24]. Previous studies have shown that DNNs can be valuable tools for decoding and reconstructing pixel-level information of natural scenes [43], [44], [47], [50], yet these studies lacked a clear correlation with established encoding metrics. Our present work aims to elucidate this tight correlation, enabling the use of DNNs to quantify neuronal response patterns and compute the differences between patterns in response to both artificial and natural stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer learning is an emerging technique in machine learning [112,113] in which a machine exploits the knowledge gained from a previous task to improve the generalizability of another [114,115] ; usually, the scale of data in the original training task is larger than that in the new problem. In this case, the advantages of transfer learning are obvious, i.e., it reduces training time, results in better neural network performance (in most cases), and does not need much data.…”
Section: Deep Neural Network Methodsmentioning
confidence: 99%